Application of E-Books from the Perspective of the Students of Teacher Education and Pedagogical Faculties in the Western Balkans - Ljiljana S. Kostić; Daliborka S. Purić (University of Belgrade, Teacher Education Faculty, 2022)
The development of electronic media and changes of the social context in the situation of the global health crisis in the field of education have resulted in an increased interest in digital resources, especially in the application of e-books in teaching. Resorting to this book format raises the question of the perspective of its application in the future changed social circumstances. The authors examine (a) the experiences of students of teacher education and pedagogical faculties (N = 394) from four countries of the Western Balkans regarding the use of digital libraries; (b) the anticipated purpose of using e-books upon the completion of their studies; (c) students' views on the universal values of books, regardless of the format in which they are published. The attitudes of these students regarding the future application of e-books is determined by their open-mindedness relative to the application of modern technologies for educational purposes, experience in using e-books, their views on the purpose of the future application of this type of books, and values regarding different book formats and books in general. The research findings show that future preschool and primary school teachers are characterized by the values that qualify them for an adequate approach to the outcomes of future changes in the development of books and modern education.